Multifunctional nitrogen-sulfur codoped carbon quantum dots: Determining reduced glutathione, broad-spectrum antibacterial activity, and cell imaging - Zhipeng Ruan; Zhifeng Xu; Tianhui Liu; Liwen Chen; Xiaoling Liu; Kaiying Chen; Chengfei Zhao (Heliyon)
In this study, nitrogen-sulfur codoped carbon quantum dots (N-S/CQDs) with various functions and properties were synthesized through a one-step method utilizing citric acid and cysteine as reaction substrates. The fluorescence of N-S/CQDs can be specifically quenched by permanganate ion (MnO4−), and the quenched fluorescence can be recovered by the presence of reduced glutathione (GSH). A fluorescence sensing system based on N-S/CQDs@MnO4− was developed and successfully applied for the determination of GSH in pharmaceutical preparations. Additionally, N-S/CQDs demonstrated broad-spectrum antibacterial activity, with minimum inhibitory concentrations of 32 μg/ml against Staphylococcus aureus (gram-positive bacterium) and 64 μg/ml against Escherichia coli (gram-negative bacterium). N-S/CQDs also proved effective for cell imaging, exhibiting excellent biocompatibility. These findings underscore the multifunctional characteristics and promising application potential of N-S/CQDs. Furthermore, this study provides a solid foundation for the development of multifunctional carbon quantum dots and the expansion of their applications in various fields.